Role for cAMP and protein phosphatase in the presynaptic expression of mouse hippocampal mossy fibre depotentiation - Huang, Chiung-Chun (Blackwell Science Inc, 2002)
Long-term potentiation (LTP) at the hippocampal mossy fibre–CA3 synapses can be reversed (depotentiated) by long trains of low-frequency stimulation (LFS). In the present study, we showed that this depotentiation is triggered by a presynaptic group II metabotropic glutamate receptor (mGluR), which reduces cytosolic cAMP level, leading to a reversal of cellular processes responsible for mossy fibre LTP expression. Furthermore, we found that both the presynaptic activity-induced elevation of Ca(2+) and the activation of protein phosphatase (PP) activity are required for the induction of depotentiation. Thus, we conclude that mossy fibre depotentiation is expressed presynaptically through the activation of both presynaptic mGluR- and PP-coupled signalling cascades, and that the bidirectional long-term plasticity at the mossy fibre–CA3 synapses is likely to be regulated by presynaptic Ca(2+)-dependent processes.